Sprouty proteins: antagonists of endothelial cell signaling and more - Cabrita, Miguel A.; Christofori, Gerhard (Thrombosis and Haemostasis, 2003)
Among many signaling pathways, receptor tyrosine kinases (RTKs) can activate the mitogen-activated protein kinase (MAPK) signaling pathway that subsequently leads to a variety of cellular changes, including proliferation, differentiation and motility. The regulation of growth factor signaling is complex, and various cell types respond differently to the same stimulus for reasons not entirely understood. The recent discovery in Drosophila of Sprouty (dSpry), an inhibitor of RTK-induced MAPK activation, provides clues to how these signals are regulated. In mammals, four orthologues of dSpry, Spry1-4, have been described, and in this review we discuss their functional characteristics. Mammalian Sprys, like dSpry, are ligand-induced feedback inhibitors of a number of growth factor receptors. In endothelial cells, upon fibroblast growth factor (FGF) receptor and vascular endothelial growth factor (VEGF) receptor activation, Sprys translocate to the plasma membrane and inhibit cell growth and proliferation. However, in epidermal growth factor (EGF)-stimulated cells, Sprys can enhance MAPK activation. In addition, Sprys have many binding partners, including different effectors of the MAPK activation pathway. The intersection point where Sprys interfere in the MAPK pathway as well as their interactions with other proteins may partly explain the dual, yet opposing roles, on growth factor-induced MAPK activation. Moreover, Sprys require tyrosine phosphorylation to interact with their binding partners, a prerequisite for their dual function. Hence, Sprys add another layer of complexity to the regulation of RTK-mediated signal transduction that begins to explain the variation in cellular responses to growth factors.This publication was partially financed by Serono Foundation for the Advancement of Medical Science.Part of this paper was originally presented at the 2nd International Workshop on New Therapeutic Targets in Vascular Biology from February 6-9, 2003 in Geneva, Switzerland.
Keywords: Sprouty; growth factors; MAPK; angiogenesis; receptor tyrosine kinases